Comparison of cases of sexual violence against children and adolescents in the period 2018-2020 (Research, Society and Development, 2021)
This study aims to compare cases of sexual violence against children and adolescents during the period of 2018-2020. This is a documentary research, analytical study, having as source of information expert reports of sexual violence produced at the Medico-Legal Institute of a capital from the Northeast in Brazil. Addressing victims aged between 0 and 18 years. The study covers from April to June of 2018 until 2020. 309 reports of sexual violence were identified during this study. In 2020, there was an increase in the percentage of male victims, aged 0 to 11 years, who were raped in their homes by family members. In 2020, there was a decline of 44.8% in reports of sexual violence when compared to the same period frame in 2019, and 37.3% when compared to 2018. The study points out to a high prevalence of child and youth sexual violence, with an increase in 2020 the percentage of aggressors with an intrafamily bond with the victim and the home as the place where the violence occurred. The number of expert reports decreased significantly in 2020, possibly due to the closure of schools and restrictions on public health care services aimed at this population due to the Covid-19 pandemic.